Dirección estratégica de AIESEC como enfoque innovador aplicable a PYMES de la Zona Metropolitana de Guadalajara. Gestión por competencias (Strategic direction of AIESEC as an innovative approach applicable to SMEs in the Guadalajara Metropolitan Area. Management by competencies) - Lafarga Canales, Lidia Berenice; Vargas Hernández, José G.; Joroba Mata, Agustín (Facultad de Contaduría Pública y Administración U.A.N.L., 2013)
Abstract: The next paper shows the successful case of a strategic management model based in competences, used by the organization Association Internationale des Étudiants en Scinces Économiques et Commerciales (AIESEC) to be implemented in small and medium enterprises located in Guadalajara’s metropolitan zone, all this, with the main purpose of improving in those areas where the firm has the opportunity to grow and become more competitive.